2019
DOI: 10.5152/istanbuljpharm.2018.412321
|View full text |Cite
|
Sign up to set email alerts
|

Plants used as painkillers in folk medicine in Turkey IV – TOOTHACHE

Abstract: Turkey has a rich plant diversity due to its geography and many of these plants are used in the treatment of various diseases. The usage of these medicinal plants has been passed down from generation to generation. Ethnobotanical studies are used to record traditional treatment methods and this information is intended to contribute to drug development studies. This study (which is the fourth article in a series focusing on plants with painkilling properties) details the plants used to combat toothache. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, there is currently a paucity of information in the scientific literature regarding the inhibitory effects of A. trichophylla and C. galaticus extracts against the key clinical enzymes namely cholinesterase, tyrosinase and α‐amylase. In ethnobotanical studies, aerial parts of the members of these genera have been used traditional purposes and thus we selected aerial parts in the current work [1,8–12] . The objective of this study is thus to identify and quantify selected bioactive compounds and document on the biological activities of extracts prepared from three different extraction techniques namely homogenizer‐assisted extraction, maceration and infusion.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there is currently a paucity of information in the scientific literature regarding the inhibitory effects of A. trichophylla and C. galaticus extracts against the key clinical enzymes namely cholinesterase, tyrosinase and α‐amylase. In ethnobotanical studies, aerial parts of the members of these genera have been used traditional purposes and thus we selected aerial parts in the current work [1,8–12] . The objective of this study is thus to identify and quantify selected bioactive compounds and document on the biological activities of extracts prepared from three different extraction techniques namely homogenizer‐assisted extraction, maceration and infusion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the wood oil had a number of traditional applications, including the treatment of leprosy 16 and catarrhal respiratory tract disorders 6 . Toothaches were also treated with cedar 10 .…”
Section: Ethnomedicinal Uses Of Cedrus Libanimentioning
confidence: 99%
“…The order is Pinales 19 . The plant is known under several common names, such as Lebanese cedar, Cedar of Lebanon, and Kamalak in southern Anatolia 10,20,21…”
Section: Classificationmentioning
confidence: 99%
“…In addition, it has been reported that the unconscious use of family members in medicine, raw materials in industry, and among the public causes an increae in cancer due to the risk factor of diterpenester (a chemical compounds) (Hecker, 1986). When the recent sources are examined (Luz et al, 2015;Mali and Jadhav, 2015;Erbay et al, 2018;Schippmann, 2018;Aylward et al, 2016;Avcı, 1993) in citotoxicity studies, especially in cancer, would healing, dental and acne treatment, industry and pharmaceutical industry, rubber extraction from latex material, dye raw material, cultivation as ornamental plant and wax making, again, it seems that the latex material has a positive effect on the application of the chemical 'Ingenol angelate' used to suppress the growth of melanoma cells.…”
Section: Usage Areasmentioning
confidence: 99%